Elevated Levels of Soluble CTLA-4, PD-1, PD-L1, LAG-3 and TIM-3 and Systemic Inflammatory Stress as Potential Contributors to Immune Suppression and Generalized Tumorigenesis in a Cohort of South African Xeroderma Pigmentosum Patients - Kgokolo, Mahlatse C. M.; Anderson, Katherine; Siwele, Shalate C.; Steel, Helen C.; Kwofie, Luyanda L. I.; Sathekge, Mike M.; Meyer, Pieter W. A.; Rapoport, Bernardo L.; Anderson, Ronald (Frontiers in Oncology, 2022)
Xeroderma Pigmentosum (XP), an autosomal recessive disorder characterized by ultraviolet radiation-induced abnormalities of DNA excision and repair pathways is associated with early development of cutaneous cancers. Intracellular oxidative stress has also been proposed as a contributor to the occurrence of skin cancers. However, little is known about the possible augmentative contributions of chronic inflammation, immune suppression and oxidative stress to the pathogenesis of malignancies associated with other subtypes of XP. This has been addressed in the current study, focused on the measurement of systemic biomarkers of inflammation, immune dysfunction and oxidative damage in XP patients, consisting of XP-C, XP-D and XP-E cases, including those XP-C cases who had already developed multiple skin malignancies. The inflammatory biomarker profile measured in XP patients and healthy control subjects included the cytokines, interleukins (ILs)-2, -4, -6, -10, interferon-γ (IFN- γ) and tumor-necrosis factor-α (TNF-α), the acute phase reactant, C-reactive protein (CRP), and cotinine (as an objective indicator of smoking status). Immune suppression was detected according to the levels of five soluble inhibitory immune checkpoint proteins (CTLA-4, PD-1, PD-L1, LAG-3 and TIM-3), as well as those of vitamin D, while oxidative stress was determined according to the circulating levels of the DNA adduct, 8-hydroxy-2-deoxyguanosine (8-OH-dG). These various biomarkers were measured in plasma using immunofluorimetric, nephelometric and ELISA procedures. Significant elevations in IL-6 (P<0.01) and TNF-α (P<0.0001), but none of the other cytokines, as well as increased levels of all five soluble inhibitory immune checkpoints (P=0.032-P=0.0001) were detected in the plasma of the XP patients. C-reactive protein and vitamin D were increased and decreased, respectively (both P<0.0001), while only one participant had an elevated level of plasma cotinine. Surprisingly, the levels of 8-OH-dG were significantly (P=0.0001) lower in the group of XP patients relative to a group of healthy control subjects. The findings of increased levels of pro-inflammatory cytokines and, in particular, those of the soluble immune checkpoints, in the setting of decreased vitamin D and moderately elevated levels of CRP in XP patients suggest a possible secondary role of ongoing, inflammatory stress and immune suppression in the pathogenesis of XP-associated malignancies.